Workplace Spirituality and Employee Well-being: An Empirical Exploration. (May 2017) - Garg, Naval
The popularity of concept of spirituality is increasing exponentially in the field of human resource management. Both academicians and practitioners are looking at spirituality to solve modern day human resource challenges. Spirituality at work is about search for meaning or higher purpose, connectedness and transcendence. The present research article addresses conceptual and empirical gap using the concept of workplace spirituality and empirically examines relationship between workplace spirituality and employee commitment, job satisfaction and work–life balance satisfaction. The article successfully augments literature by suggesting one more dimension (Karma Capital) of Indian spiritual values. This is one of the pioneer studies that used necessary condition analysis (NCA) to explore workplace spirituality. Workplace spirituality was reported as a necessary determinant of employee commitment, job satisfaction and work–life balance satisfaction. Relationship between these variables is further investigated through correlation matrix and regression analysis.